Relationship between education and utilization of maternal health care services by pregnant women in Ibadan north local government, Oyo state (2019)
This study examined the relationship between education and maternal Health care utilization among pregnant women attending maternity centres in Ibadan. Descriptive survey research design was adopted far the study. The sample study was selected from pregnant women attending maternity centres in the ten wards of Ibadan North Local Government. A sample of 120 pregnant women was randomly selected far the study. A structured questionnaire was used to collect data. The data were analyzed using Pearson Product Moment Correlation. The study revealed that there was significant relationship between basic education and utilization of maternal health Services (r = .821, n= 120, P < .05).). It also showed that there was significant relationship between higher education and utilization of maternal health care Services (r- .856, N= 120, P<.05). Based on these findings, it was recommended that interventions to improve the utilization of maternal health care Services by women should include targeting women far medical outreach and health education. Uneducated women should be enlightened on basic and higher education